Two-dimensional porphyrin-based MOF (Metal Organic Framework) layered nano-channel film as well as preparation method and application thereof
By introducing chelating agents and interlayer restricted transport channels into the two-dimensional porphyrin-based MOF layered nanochannel membrane, combined with the porous structure of MOF, the problem of limited ion separation performance of two-dimensional layered membrane in the prior art is solved, and the problem of limited ion separation performance of two-dimensional layered membranes is achieved. Efficient ion separation effect.
Patent Information
- Application Number
- CN202411532911.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-07
AI Technical Summary
The existing two-dimensional layered membranes have limited performance in ion separation performance, and the existing MOF ion separation membranes only use the porous structure of MOF itself and lack interlayer restricted transmission channels.
Two-dimensional porphyrin-based MOF nanosheets are stacked layer by layer, and a chelating agent with cation recognition ability is modified on the surface of the nanosheets to form a layered nanochannel membrane. The membrane combines the porous structure of MOF and the interlayer restricted transport channel, and improves the selectivity and efficiency of ion separation through the complexation reaction of chelating agents with cations.
Effective separation of cations of different valence states is achieved, and the ion separation efficiency is further improved through photothermal response, significantly improving the technical difficulties of limited ion separation efficiency in the prior art.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of thin film preparation and separation and purification, and in particular relates to a two-dimensional porphyrin-based MOF layered nanochannel membrane for ion separation, a preparation method and an application thereof. Background Art
[0002] Membrane separation technology is a green and clean separation and purification technology that can separate cations of different valence states. It is widely used in the fields of lithium extraction from salt lakes, rare earth element extraction, salt difference energy recovery, etc., and plays an increasingly important role in economic and social development.
[0003] Separation membrane is the core component of membrane separation technology. In recent years, two-dimensional layered membranes have shown great potential in the field of ion separation due to their angstrom-level restricted transmission channels. At present, materials such as MXene, GO, hydrotalcite, and montmorillonite have been widely used to prepare two-dimensional layered membranes. For example, Chinese patent application CN117983077A discloses a Co-Al hydrotalcite two-dimensional nanochannel membrane for monovalent cation separation, and Chinese patent application CN 117323841A discloses a montmorillonite-based separation membrane for monovalent cation separation. The nanosheets prepared using traditional materials such as hydrotalcite and montmorillonite are non-porous structures. Therefore, the corresponding two-dimensional layered membranes only rely on the two-dimensional interlayer confined channels formed by the nanosheets during the stacking process for ion separation, and their ion separation performance is very limited. As an ideal building unit for separation membranes, MOF itself has a porous structure and is believed to be able to effectively solve the above problems. For example, Chinese patent application CN 107398186 B discloses a metal organic framework separation membrane for ion separation, and Chinese patent application CN 117839451 A discloses a MOF-On-MOF composite ion separation membrane. However, in the preparation process of the MOF ion separation membranes reported above, MOF grows on the substrate surface through chemical reaction, and only utilizes the porous structure of MOF itself during ion separation, and does not have the interlayer restricted transmission channel of the traditional two-dimensional layered membrane, and its ion separation performance also shows limitations. Summary of the invention
[0004] In view of the defects and shortcomings of the prior art, the purpose of the present invention is to provide a two-dimensional porphyrin-based MOF layered nanochannel membrane, a preparation method and application, so as to solve the technical problem that the two-dimensional layered membrane has limited ion separation performance in the prior art.
[0005] The present invention is achieved through the following technical solutions: The invention provides a two-dimensional porphyrin-based MOF layered nanochannel membrane, comprising two-dimensional porphyrin-based MOF nanosheets, wherein the two-dimensional porphyrin-based MOF nanosheets are stacked layer by layer, and the two-dimensional porphyrin-based MOF nanosheets are modified with a chelating agent having cation recognition ability.
[0006] Preferably, the two-dimensional porphyrin-based MOF nanosheet is a two-dimensional Cu-TCPP MOF nanosheet, a two-dimensional Fe-TCPP MOF nanosheet or a two-dimensional Zn-TCPP MOF nanosheet.
[0007] Preferably, the chelating agent is ethylenediaminetetraacetic acid, citric acid, 15-crown-5-ether, 12-crown-4-ether, 18-crown-6-ether, α-cyclodextrin, β-cyclodextrin or γ-cyclodextrin.
[0008] The method for preparing the two-dimensional porphyrin-based MOF layered nanochannel membrane of the present invention comprises the following steps: S1, adding a chelating agent solution having cation recognition ability dropwise into a two-dimensional porphyrin-based MOF nanosheet solution, stirring, and obtaining a modified two-dimensional porphyrin-based MOF nanosheet solution; S2, depositing the modified two-dimensional porphyrin-based MOF nanosheet solution onto the substrate surface to obtain a two-dimensional porphyrin-based MOF layered nanochannel membrane.
[0009] Preferably, in S1, the preparation method of the two-dimensional porphyrin-based MOF nanosheet solution is: Dissolving metal salt and pyrazine in a mixed solution of DMF and ethanol to obtain a metal solution; dissolving porphyrin in a DMF solution to obtain a ligand solution; The metal solution and the ligand solution are mixed and heated for reaction; after the reaction is completed, the solution is washed by centrifugation to obtain a bulk crystal precipitate; the bulk crystal precipitate is dispersed in anhydrous ethanol for ultrasonic exfoliation, and a two-dimensional porphyrin-based MOF nanosheet solution is obtained after centrifugation.
[0010] Furthermore, a two-dimensional porphyrin-based MOF nanosheet solution is obtained after centrifugation, specifically: centrifugation at 3000-5000 rpm, taking the supernatant, centrifuging the supernatant at 8500-10000 rpm, taking the lower layer of liquid, and obtaining a two-dimensional porphyrin-based MOF nanosheet solution.
[0011] Preferably, in S2, the substrate is one of a polyvinylidene fluoride membrane, an anodized aluminum filter membrane, a nylon membrane and a mixed cellulose ester membrane.
[0012] Preferably, in S2, the modified two-dimensional porphyrin-based MOF nanosheet solution is deposited onto the substrate surface by one of a filtration method, a layer-by-layer self-assembly method, a spin coating method, a drop coating method and a spray coating method.
[0013] The present invention provides the use of the two-dimensional porphyrin-based MOF layered nanochannel membrane as described above in ion separation.
[0014] Preferably, during the ion separation process, a light source is used to irradiate the two-dimensional porphyrin-based MOF layered nanochannel membrane on the permeation side of the two-dimensional porphyrin-based MOF layered nanochannel membrane.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention uses two-dimensional porphyrin-based MOF nanosheets with an inherent porous structure as a building unit to prepare a layered nanochannel membrane. Compared with traditional two-dimensional membranes and existing publicly reported MOF separation membranes, the two-dimensional porphyrin-based MOF layered nanochannel membrane of the present invention has both interlayer confined transmission channels and pore structures, and the synergistic effect of the two can achieve effective separation of ions; and, the present invention grafts a chelating agent on the surface of the MOF nanochannel wall, which can react with specific cations to reduce the transmission rate of specific ions, thereby improving the selectivity of ions with different valence states and improving the ion separation efficiency. Therefore, the present invention is based on the synergistic effect of the complexation reaction of the two-dimensional interlayer confined transmission channel, the inherent pore structure of MOF and the chelating agent, which effectively improves the technical problem of limited ion separation efficiency in the prior art. In addition, based on the photothermal response of porphyrin, a temperature field is formed in the nanochannel after irradiation with a light source, which can provide a driving force for ion transmission and effectively improve the ion separation efficiency.
[0016] The preparation method of the two-dimensional porphyrin-based MOF layered nanochannel membrane of the present invention effectively regulates the interaction between metal ions and porphyrin ligands by introducing pyrazine, thereby inhibiting the longitudinal growth of crystals. Therefore, the growth rate in the horizontal direction is higher than the growth rate in the vertical direction, and finally a block crystal with a multilayer structure is generated. Subsequently, a single-layer two-dimensional porphyrin-based MOF nanosheet can be obtained by ultrasonic mechanical stripping.
[0017] Furthermore, the preparation method of the present invention can obtain large-layer nanosheets by first centrifuging at a low speed and then at a high speed. By constructing a nanochannel membrane with the large-layer nanosheets, more regular nanochannels can be formed.
[0018] Benefiting from the synergistic effect of MOF inherent pore size, two-dimensional interlayer confined transmission channel and chelating agent, the two-dimensional porphyrin-based MOF layered nanochannel membrane of the present invention can achieve effective separation between anions and cations, and between cations of different valence states. In addition, based on the photothermal effect of porphyrin, the ion separation efficiency can be further improved after illumination. The present invention can be applied to the fields of salinity energy recovery, lithium extraction from salt lakes, extraction of rare earth elements, and resource treatment of industrial pickling wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0020] Figure 1 This is a scanning electron microscope image of the two-dimensional porphyrin-based MOF layered nanochannel membrane prepared in Example 1.
[0021] Figure 2 It is the Fourier infrared spectra of the two-dimensional porphyrin-based MOF layered nanochannel membranes prepared in Example 1 and Comparative Example 1.
[0022] Figure 3 3 is a comparison chart of the lithium ion selectivity of the two-dimensional porphyrin-based MOF layered nanochannel membrane prepared in Example 1 and Comparative Example 1.
[0023] Figure 4 3 is a comparison chart of the potassium ion selectivity of the two-dimensional porphyrin-based MOF layered nanochannel membrane prepared in Example 1 and Comparative Example 1.
[0024] Figure 5 is the binding energy between the two-dimensional porphyrin-based MOF layered nanochannel membrane prepared in Example 1 and cations of different valence states. DETAILED DESCRIPTION
[0025] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0026] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.
[0027] It should be noted that the terms "include" and "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to define the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.
[0028] The two-dimensional porphyrin-based MOF layered nanochannel membrane provided by the present invention comprises two-dimensional porphyrin-based MOF nanosheets, wherein the two-dimensional porphyrin-based MOF nanosheets are stacked layer by layer, and the two-dimensional porphyrin-based MOF nanosheets are modified with a chelating agent having cation recognition ability.
[0029] In some specific embodiments of the present invention, the two-dimensional porphyrin-based MOF nanosheet is a two-dimensional Cu-TCPP MOF nanosheet, a two-dimensional Fe-TCPP MOF nanosheet, a two-dimensional Zn-TCPP MOF nanosheet, or the like.
[0030] In some specific embodiments of the present invention, the chelating agent is ethylenediaminetetraacetic acid (EDTA), citric acid, 15-crown-5-ether, 12-crown-4-ether, 18-crown-6-ether, α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, etc. Different chelating agents recognize different types of cations.
[0031] The method for preparing the two-dimensional porphyrin-based MOF layered nanochannel membrane of the present invention comprises the following steps: S1, adding a chelating agent solution having cation recognition ability dropwise into a two-dimensional porphyrin-based MOF nanosheet solution, and continuously stirring to obtain a modified two-dimensional porphyrin-based MOF nanosheet solution; S2, depositing the modified two-dimensional porphyrin-based MOF nanosheet solution onto the substrate surface to obtain a two-dimensional porphyrin-based MOF layered nanochannel membrane.
[0032] In S1 of the present invention, the method for preparing the two-dimensional porphyrin-based MOF nanosheet solution comprises: Step 1, dissolving a metal salt and pyrazine in a mixed solution of DMF and ethanol to obtain a metal solution; dissolving porphyrin in a DMF solution to obtain a ligand solution: Step 2, mixing the metal solution and the ligand solution, and heating them to react; Step 3, after the reaction is completed, the mixture is washed by centrifugation to obtain a block crystal precipitate; the block crystal precipitate is dispersed in anhydrous ethanol and ultrasonically exfoliated, and a two-dimensional porphyrin-based MOF nanosheet solution is obtained after centrifugation.
[0033] In some specific embodiments of the present invention, the metal salt is copper nitrate, iron nitrate or zinc nitrate; the mass ratio of the metal salt to pyrazine is (5-20) mg: 5 mg, and the mixing ratio of DMF to ethanol is (25-75) mL: 25 mL.
[0034] In some specific embodiments of the present invention, the concentration of the ligand solution is 0.5-3.5 mg / mL, and the molar ratio of the metal to the ligand porphyrin is: (1-3) mol:1 mol.
[0035] In some specific embodiments of the present invention, in step 2, the heating temperature is 120° C. and heating is performed in an oil bath.
[0036] In some specific embodiments of the present invention, in step 3, the ultrasonic stripping time is 30-240 min.
[0037] The present invention obtains a two-dimensional porphyrin-based MOF nanosheet solution by centrifugation, which can be done in two ways. One implementation method is: the rotation speed of the centrifugation after the ultrasonic peeling is 8500-10000 rpm, the centrifugation time is 30-60 min, and the supernatant is taken. The number of centrifugation depends on the color of the supernatant. If the supernatant is transparent after the centrifugation, and there is a purple precipitate below, the supernatant needs to be poured out, and the purple precipitate is redispersed in anhydrous ethanol. Repeat the above centrifugation steps until the supernatant is purple, indicating that the two-dimensional porphyrin-based MOF nanosheet is successfully peeled off.
[0038] Another embodiment is: after centrifugation, a two-dimensional porphyrin-based MOF nanosheet solution is obtained, specifically: centrifugation at 3000-5000 rpm, taking the supernatant, centrifuging the supernatant at 8500-10000 rpm, taking the lower layer of liquid, and obtaining a large-layer two-dimensional porphyrin-based MOF nanosheet solution. The large-layer nanosheets screened by this method are used to construct a nanochannel membrane, which can form a more regular nanochannel.
[0039] In S1 of the present invention, the concentration of the chelating agent solution having cation recognition ability is 0.25-1.5 mg / mL.
[0040] In S2 of the present invention, the continuous stirring time is 1-24 h.
[0041] In S2 of the present invention, when the modified two-dimensional porphyrin-based MOF nanosheet solution is deposited on the surface of a substrate, one of a filtration method, a layer-by-layer self-assembly method, a spin coating method, a drop coating method and a spray coating method is adopted; the substrate is one of a polyvinylidene fluoride membrane (PVDF), an anodized aluminum filter membrane, a nylon membrane and a mixed cellulose ester membrane.
[0042] The two-dimensional porphyrin-based MOF layered nanochannel membrane of the present invention can be used to separate cations of different valence states, and can also achieve effective separation of anions and cations.
[0043] In order to further improve the ion separation efficiency, during ion separation, light-driven ion separation can be used based on the photothermal response of porphyrin itself, that is, during the ion separation process, a light source is used to irradiate the two-dimensional porphyrin-based MOF layered nanochannel membrane on the permeable side of the two-dimensional porphyrin-based MOF layered nanochannel membrane.
[0044] In accordance with the above technical scheme, specific embodiments of the present invention are given below. It should be noted that the present invention is not limited to the following specific embodiments, and all equivalent changes made on the basis of the technical scheme of this application fall within the protection scope of the present invention.
[0045] Embodiment 1: This embodiment provides a method for preparing a two-dimensional porphyrin-based MOF layered nanochannel membrane for ion separation, and the preparation method specifically comprises the following steps: Step 1: Dissolve 20 mg of copper nitrate and 5 mg of pyrazine in a mixed solution of 70 mL of N,N-dimethylformamide (DMF) and 25 mL of ethanol at room temperature to obtain a metal solution. Further, dissolve 100 mg of porphyrin in 100 mL of DMF solution to obtain a ligand solution. Mix 15 mL of the metal solution with 10 mL of the ligand solution and heat to 120°C in an oil bath for 6 h. After the reaction is completed, centrifuge and wash at 8500 rpm for 30 min, then pour off the supernatant to remove impurities that have not reacted sufficiently to obtain a purple precipitate. Disperse the purple precipitate in DMF again, and repeat the centrifugal washing step 3 times. Disperse the washed purple precipitate in anhydrous ethanol solution and ultrasonically peel for 60 min. After centrifugation at 8500 rpm for 60 min, a Cu-TCPP MOF nanosheet solution is prepared.
[0046] Step 2: Add 1 mg / mL EDTA solution dropwise to the above two-dimensional Cu-TCPP MOF nanosheet solution and continue stirring at room temperature for 24 hours to obtain a modified Cu-TCPP MOF nanosheet solution.
[0047] Step three, using vacuum filtration, the modified Cu-TCPP MOF nanosheet solution in step two is stacked layer by layer on a PVDF substrate with a pore size of 220 nm to obtain a two-dimensional EDTA@Cu-TCPPMOF layered membrane with the ability to separate cations of different valence states, that is, a two-dimensional porphyrin-based MOF layered nanochannel membrane.
[0048] The cross-sectional view of the EDTA@Cu-TCPP MOF layered membrane prepared in this example is shown in FIG. Figure 1 As shown, it can be seen that the modified Cu-TCPP MOF nanosheets are stacked in parallel on the substrate surface, forming a large number of interlayer nano-confined transmission channels.
[0049] Comparative Example 1: The difference between this comparative example and Example 1 is that the preparation process of this comparative example does not perform step 2, and the Cu-TCPP MOF nanosheet solution in step 1 is stacked layer by layer on a PVDF substrate with a pore size of 220 nm to obtain a Cu-TCPP MOF layered membrane, and the rest of the process is the same as Example 1.
[0050] Figure 2 The Fourier transform infrared spectra of the two-dimensional porphyrin-based MOF layered nanochannel membranes prepared in Example 1 and Comparative Example 1 show that both the Cu-TCPP MOF and EDTA@Cu-TCPP MOF layered membranes have -OH, CN, and Cu-N characteristic peaks. The difference is that the CN peak of EDTA@Cu-TCPP MOF is lower than that of Cu-TCPP MOF from 1270 cm -1 Shifted to 1256 cm -1 , which shows that the EDTA modification in Example 1 is successful.
[0051] Application example 1: Lithium ion separation The EDTA@Cu-TCPP MOF and Cu-TCPP MOF layered membranes prepared in Example 1 and Comparative Example 1 were placed in a U-shaped filtration device, with pure water on the permeable side of the layered membrane and 0.5 M lithium chloride, magnesium chloride, calcium chloride, and aluminum chloride solutions on the stock solution side.
[0052] like Figure 3 As shown, the lithium ion / high-valent cation selectivity comparison diagram of the layered membranes of Example 1 and Comparative Example 1. It can be seen that the EDTA@Cu-TCPP MOF layered membrane in Example 1 has a good selectivity for Li + / Mg 2+ , Li + / Ca 2+ , Li + / Al 3+The selectivities of Li are 15.34, 13.4 and 26.18 respectively, which are significantly better than the Cu-TCPP layered membrane in Comparative Example 1, which are 1.56, 1.63 and 1.7 times higher than the Cu-TCPP layered membrane in Comparative Example 1. + / Al 3+ The separation coefficient is even as high as 95%. It can be seen that the Li + The selectivity is significantly improved, effectively realizing Li + With Mg 2+ , Ca 2+ and Al 3+ separation.
[0053] Application Example 2: Potassium Ion Separation The difference between this application example and application example 1 is that in this application example, the stock solution side is immersed in 0.5M potassium chloride, magnesium chloride, calcium chloride, and aluminum chloride solutions in sequence.
[0054] like Figure 4 As shown, it is a comparison of the potassium ion / high-valent cation selectivity of the layered membranes of Example 1 and Comparative Example 1. It can be seen that the K + / Mg 2+ , K + / Ca 2+ , K + / Al 3+ The selectivities of K are 20.27, 17.02 and 34.68, respectively, which are significantly better than those of the Cu-TCPP layered membrane in Comparative Example 1, which are 1.73, 1.75 and 1.86 times higher than those of the Cu-TCPP layered membrane in Comparative Example 1. + / Mg 2+ and K + / Al 3+ The separation coefficient is even as high as 95%. It can be seen that the K of the EDTA@Cu-TCPP MOF layered membrane of Example 1 is higher than that of the Cu-TCPP MOF layered membrane of Comparative Example 1. + The selectivity is significantly improved, effectively achieving K + With Mg 2+ , Ca 2+ and Al 3+ Separation.
[0055] like Figure 5 As shown, DFT calculations prove that K + , Li + , Ca 2+ Mg 2+The binding energies of ions with EDTA on the surface of Cu-TCPP nanochannel walls are -9.04 eV, -10.90 eV, -16.13 eV, and -35.14 eV, respectively, which indicates that divalent cations have a stronger affinity with EDTA, making it more difficult for divalent cations to be transported through the nanochannel. Therefore, EDTA@Cu-TCPP MOF layered membranes exhibit better monovalent / high-valent cation separation performance than Cu-TCPP MOF layered membranes.
[0056] Application Example 3: Light-driven Lithium Ion Separation The difference between this application example and application example 1 is that in this application example, the layered film is irradiated on the transmission side using a xenon lamp.
[0057] The results show that the Li + / Mg 2+ , Li + / Ca 2+ , Li + / Al 3+ The selectivities are 28.34, 22.21 and 40.78, respectively, which are 1.84, 1.65 and 1.55 times higher than those in Application Example 1. This is mainly due to the fact that, after irradiation with the xenon lamp, a temperature field is formed in the nanochannel, which provides an effective driving force for lithium ion transport.
[0058] Application example 4: Rare earth ion separation The difference between this application example and application example 1 is that in this application example, the stock solution side is immersed in 0.5M lanthanum chloride and cerium chloride solutions in sequence.
[0059] The results show that the La content of the EDTA@Cu-TCPP MOF layered membrane in Example 1 is 3+ / Ce 3+ The selectivity is 27.45, while the La 3+ / Ce 3+ The selectivity is 7.45. It can be seen that the selectivity of rare earth ions can be effectively improved by EDTA modification.
[0060] Application example 5: Resource utilization of industrial pickling wastewater The difference between this application example and application example 1 is that in this application example, the stock solution side is immersed in 1 M hydrochloric acid and 0.2 MFeCl2 in sequence.
[0061] The results show that the separation factor of hydrogen ions of the EDTA@Cu-TCPP MOF layered membrane in Example 1 is 75, while the separation factor of the Cu-TCPP MOF layered membrane in Comparative Example 1 is 45.
[0062] Embodiment 2: The difference between this embodiment and embodiment 1 is that the metal salt in step 1 of this embodiment is ferric nitrate. The two-dimensional layered membrane prepared in this embodiment is EDTA@Fe-TCPP MOF, and its lithium ion and potassium ion selectivity is basically the same as that in embodiment 1. Specifically, the EDTA@Fe-TCPP MOF layered membrane has a good selectivity for Li + / Mg 2+ , Li + / Ca 2+ , Li + / Al 3+ The selectivities of K + / Mg 2+ , K + / Ca 2+ , K + / Al 3+ The selectivities were 19.78, 18.10 and 34.17 respectively.
[0063] Embodiment 3: The difference between this embodiment and embodiment 1 is that the metal salt in step 1 of this embodiment is zinc nitrate. The two-dimensional layered film prepared in this embodiment is EDTA@Zn-TCPP MOF, and its lithium ion and potassium ion selectivity is basically the same as that in embodiment 1. Specifically, EDTA@Zn-TCPP MOF has a good selectivity for Li + / Mg 2+ , Li + / Ca 2+ , Li + / Al 3+ The selectivities of K + / Mg 2+ , K + / Ca 2+ , K + / Al 3+ The selectivities were 21.22, 17.95 and 36.54 respectively.
[0064] Embodiment 4: The difference between this embodiment and embodiment 1 is that the centrifugation conditions for screening Cu-TCPP nanosheets are different.
[0065] In step 1 of this embodiment, the supernatant is first obtained by centrifugation at 4000 rpm for 30 minutes, and then the supernatant is further centrifuged at 8500 rpm for 30 minutes. At this time, the upper part of the centrifuge tube is a small-layer nanosheet solution, and the bottom is a large-layer nanosheet. The upper liquid is poured out, and the large-layer nanosheet at the bottom is used to construct a two-dimensional layered membrane.
[0066] In Example 1, a Cu-TCPP nanosheet solution can be obtained after 8500rpm and 60min, and the nanosheets are mainly small sheets (with smaller lateral dimensions). In this embodiment, the nanosheet solution is first collected at a low speed of 4000rpm. At this time, the solution will have more large-sheet nanosheets (with larger lateral dimensions) than in Example 1. This is because, in theory, the mass of large-sheet nanosheets is relatively larger than that of small-sheet nanosheets. Therefore, under high-speed conditions, large-sheet nanosheets with relatively larger mass will be dispersed at the bottom, while small-sheet nanosheets with relatively smaller mass will be dispersed at the top. Based on this, in this embodiment, the supernatant collected after centrifugation at 4000 rpm contains large-sheet and small-sheet nanosheets. Further, the supernatant is centrifuged at 8500rpm, and the upper liquid is small-sheet nanosheets, while large-sheet nanosheets are dispersed at the bottom. In this embodiment, large-sheet nanosheets at the bottom are used to construct nanochannel membranes.
[0067] The Li + / Mg 2+ , Li + / Ca 2+ , Li + / Al 3+ The selectivities are 22.25, 18.10 and 37.55, respectively, which are 1.45, 1.37 and 1.43 times the selectivity of the two-dimensional layered membrane in Example 1. This is mainly because the nanosheets in this example have larger lateral dimensions after centrifugal screening, and more regular nanochannels can be formed in the process of stacking and curing to form a film, with fewer structural defects, which reduces the ion transmission resistance and improves the ion selectivity.
[0068] Embodiment 5: The difference between this example and Example 1 is that in step 2 of this example, 1 mg / mL of 15-crown-5-ether solution is added dropwise to the two-dimensional Cu-TCPP MOF nanosheet solution. + / Mg 2+ , K + / Ca 2+ , K + / Al 3+ The selectivities were 23.10, 22.52 and 38.42, respectively, which were 1.13, 1.32 and 1.10 times the selectivity of the two-dimensional layered membrane in Example 1, and 1.97, 2.32 and 2.06 times the selectivity of the two-dimensional layered membrane in Comparative Example 1. This is mainly due to the 2:1 ring structure of 15-crown-5 ether, which can specifically bind to potassium ions to accelerate their transmission speed.
[0069] Embodiment 6: The difference between this example and Example 1 is that in step 2 of this example, 1 mg / mL of 12-crown-4 ether solution is added dropwise to the two-dimensional Cu-TCPP MOF nanosheet solution. + / Mg 2+ , Li + / Ca 2 + , Li + / Al 3+ The selectivities were 21.20, 15.14 and 29.22, respectively, which were 1.38, 1.15 and 1.11 times the selectivity of the two-dimensional layered membrane in Example 1, and 2.16, 1.84 and 1.89 times the selectivity of the two-dimensional layered membrane in Comparative Example 1. This is mainly because 12-crown-4 ether can specifically bind to lithium ions to accelerate their transmission speed.
[0070] Embodiment 7: The difference between this embodiment and embodiment 1 is that in step 2 of this embodiment, 1 mg / mL of β-cyclodextrin solution is added dropwise to the two-dimensional Cu-TCPP MOF nanosheet solution. + / Mg 2+ , Li + / Ca 2 + , Li + / Al 3+ The selectivities were 25.12, 18.33 and 34.52, respectively, which were 1.63, 1.39 and 1.31 times the selectivity of the two-dimensional layered membrane in Example 1, respectively, and 2.56, 2.23 and 2.24 times the selectivity of the two-dimensional layered membrane in Comparative Example 1, respectively.
[0071] Embodiment 8: The difference between this embodiment and embodiment 1 is that in step 2 of this embodiment, 1 mg / mL of γ-cyclodextrin solution is added dropwise to the two-dimensional Cu-TCPP MOF nanosheet solution. + / Mg 2+ , Li + / Ca 2+ , Li + / Al 3+ The selectivities were 29.33, 25.10 and 33.78, which were 1.91, 1.87 and 1.29 times the selectivity of the two-dimensional layered membrane in Example 1, respectively.
[0072] The present invention is applied in the field of membrane separation. In addition to the separation of cations of different valence states mentioned in the above embodiments, the obtained two-dimensional porphyrin-based MOF layered nanochannel membrane can also be used to achieve effective separation of anions and cations, and can be applied to the fields of lithium extraction from salt lakes, rare earth element extraction, salt difference energy recovery, and resource treatment of industrial pickling wastewater.
Claims
1. A two-dimensional porphyrin-based MOF layered nanochannel membrane, characterized in that: It comprises two-dimensional porphyrin-based MOF nanosheets, wherein the two-dimensional porphyrin-based MOF nanosheets are stacked layer by layer, and the two-dimensional porphyrin-based MOF nanosheets are modified with a chelating agent having cation recognition ability.
2. The two-dimensional porphyrin-based MOF layered nanochannel membrane according to claim 1, characterized in that: The two-dimensional porphyrin-based MOF nanosheet is a two-dimensional Cu-TCPP MOF nanosheet, a two-dimensional Fe-TCPP MOF nanosheet or a two-dimensional Zn-TCPP MOF nanosheet.
3. The two-dimensional porphyrin-based MOF layered nanochannel membrane according to claim 1, characterized in that: The chelating agent is ethylenediaminetetraacetic acid, citric acid, 15-crown-5-ether, 12-crown-4-ether, 18-crown-6-ether, α-cyclodextrin, β-cyclodextrin or γ-cyclodextrin.
4. The method for preparing the two-dimensional porphyrin-based MOF layered nanochannel membrane according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, adding a chelating agent solution having cation recognition ability dropwise into a two-dimensional porphyrin-based MOF nanosheet solution, stirring, and obtaining a modified two-dimensional porphyrin-based MOF nanosheet solution; S2, depositing the modified two-dimensional porphyrin-based MOF nanosheet solution onto the substrate surface to obtain a two-dimensional porphyrin-based MOF layered nanochannel membrane.
5. The method for preparing a two-dimensional porphyrin-based MOF layered nanochannel membrane according to claim 4, characterized in that: In S1, the preparation method of the two-dimensional porphyrin-based MOF nanosheet solution is: Dissolving metal salt and pyrazine in a mixed solution of DMF and ethanol to obtain a metal solution; dissolving porphyrin in a DMF solution to obtain a ligand solution; The metal solution and the ligand solution are mixed and heated for reaction; after the reaction is completed, the solution is washed by centrifugation to obtain a bulk crystal precipitate; the bulk crystal precipitate is dispersed in anhydrous ethanol for ultrasonic exfoliation, and a two-dimensional porphyrin-based MOF nanosheet solution is obtained after centrifugation.
6. The method for preparing the two-dimensional porphyrin-based MOF layered nanochannel membrane according to claim 5, characterized in that: After centrifugation, a two-dimensional porphyrin-based MOF nanosheet solution is obtained, specifically: centrifugation at 3000-5000 rpm, taking the supernatant, centrifuging the supernatant at 8500-10000 rpm, taking the lower layer of liquid, and obtaining a two-dimensional porphyrin-based MOF nanosheet solution.
7. The method for preparing a two-dimensional porphyrin-based MOF layered nanochannel membrane according to claim 4, characterized in that: In S2, the substrate is one of a polyvinylidene fluoride membrane, an anodized aluminum filter membrane, a nylon membrane and a mixed cellulose ester membrane.
8. The method for preparing a two-dimensional porphyrin-based MOF layered nanochannel membrane according to claim 4, characterized in that: In S2, the modified two-dimensional porphyrin-based MOF nanosheet solution is deposited onto the substrate surface by one of a filtration method, a layer-by-layer self-assembly method, a spin coating method, a drop coating method, and a spray coating method.
9. Use of the two-dimensional porphyrin-based MOF layered nanochannel membrane according to any one of claims 1 to 3 in ion separation.
10. The use according to claim 9, characterized in that: In the process of ion separation, the two-dimensional porphyrin-based MOF layered nanochannel membrane is irradiated with a light source on the permeation side of the two-dimensional porphyrin-based MOF layered nanochannel membrane.
Citation Information
Patent Citations
Metal-organic framework separation membrane and its preparation method
CN107398186B
Preparation method and application of monovalent cation selective separation membrane of montmorillonite-based two-dimensional nano ion transmission channel
CN117323841A
MOF-On-MOF structure composite ion separation membrane with crosslinking-metal ion system as well as preparation method and application of MOF-On-MOF structure composite ion separation membrane
CN117839451A
Two-dimensional positively-charged sub-nano channel film for monovalent cation separation and preparation method and application of two-dimensional positively-charged sub-nano channel film
CN117983077A
Cited By
Conductive MOF (Metal Organic Framework) layered mineral ion channel membrane as well as preparation method and application thereof
CN121266386A
Conductive MOF@layered mineral ion channel membrane, preparation method and application thereof
CN121266386B